“Knowing Who We Are. It’s One of the Most Important Things”: Exploring Identity and Mino-Bimaadiziwin With Algonquin Anishinaabekwewag and Gender-Diverse People from Mattawa and North Bay, Ontario - Patterson, Kaitlyn; Morcom, Lindsay; Labreche, Karen; St. Amant, Deborah (Turtle Island Journal of Indigenous Health, 2024)
Indigenous identity is an important aspect of health. For Anishinaabeg, identity contributes to Mino-Bimaadiziwin (the Good Life), which involves individuals becoming their fullest selves supported by their holistic wellness (i.e. mind, body, spirit, heart), in relationship to people, place, and all our relatives. However, Algonquin identity has been deeply impacted by over 400 years of settler colonialism. Colonialism has disrupted Algonquin people’s connections to land, as well as their kinships, cultures, and communities – all of which inform Algonquin identity. Further, domestic law and policy have altered definitions of Indigeneity in Canada and imposed racist and heteropatriarchal structures that oppress and threaten Indigenous women and gender-diverse people in particular. Indigenous storytelling has been a way for Indigenous peoples to combat colonial narratives imposed upon them. It is a method of truth-telling – an opportunity to honour and uplift Indigenous experience. Therefore, this project utilizes storytelling through the conversational method to explore Algonquin identity among 13 Algonquin women and gender-diverse people from Mattawa and North Bay, Ontario. Results demonstrate diverse, complex histories of displacement and cultural resurgence, and explore embodiments of gender, sexuality, and Indigeneity that are actively being lived out while firmly rooted in a shared history. More Algonquin stories are need to further explore identity as an important component of Mino-Bimaadiziwin.